Optimized Anchor-Modified Peptides Targeting Mutated RAS Are Promising Candidates for Immunotherapy - Baleeiro, Renato B.; Dunmall, Louisa S. Chard; Liu, Peng; Lu, Shuangshuang; Lone, Yuchun; Lemoine, Nicholas R.; Wang, Yaohe (Frontiers in Immunology, 2022)
RAS mutations occur in approximately 20% of all cancers and given their clonality, key role as driver mutation, association with poor prognosis and undruggability, they represent attractive targets for immunotherapy. We have identified immunogenic peptides derived from codon 12 mutant RAS (G12A, G12C, G12D, G12R, G12S and G12V), which bind to HLA-A*02:01 and HLA-A*03:01 and elicit strong peptide-specific CD8+ T cell responses, indicating that there is an effective CD8+ T-cell repertoire against these mutant RAS-derived peptides that can be mobilized. Alterations in anchor residues of these peptides enhanced their binding affinity to HLA-A*02:01 molecules and allowed generation of CD8+ T cells that responded to target cells pulsed with the anchor-modified and also with the original peptide. Cytotoxic T cells generated against these peptides specifically lysed tumor cells expressing mutant RAS. Vaccination of transgenic humanized HLA-A2/DR1 mice with a long peptide encompassing an anchor-modified 9-mer G12V epitope generated CD8+ T cells reactive to the original 9-mer and to a HLA-A*02:01-positive human cancer cell line harboring the G12V mutation. Our data provide strong evidence that mutant RAS can be targeted by immunotherapy.